Higher Incidence of Post-traumatic Radiographic Osteoarthritis with Transtibial Femoral Tunnel Positioning Compared to Anteromedial Femoral Tunnel Positioning During Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis (208). Issue 10 (31st October 2021) - Cinque, Mark; Kunze, Kyle; Williams, Brady; Moatshe, Gilbert; LaPrade, Robert; Chahla, Jorge
Objectives: Anteromedial (AM) femoral tunnel positioning in anterior cruciate ligament reconstruction (ACLR) has been reported by some authors to yield superior clinical and functional outcomes compared to the transtibial (TT) approach; however, differences in the subsequent rates of post-traumatic osteoarthritis (PTOA) incidence are not clear. To perform a systematic review and meta-analysis of the literature to evaluate the influence of femoral tunnel positioning during primary ACLR on the development of radiographic PTOA. Methods: The Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, PubMed (1980-2019), and MEDLINE (1980-2019) were queried for all studies describing the development of PTOA following TT or AM ACLR. Data pertaining to patient demographics, ACLR technique, and radiographic PTOA were extracted. Meta-analysis utilizing the DerSimonian Laird method for random effects was used to compare the weighted proportion of PTOA after ACLR between the TT and AM approaches. Results: Sixteen studies were identified for inclusion with a total of 1, 546 patients. The mean follow-up across all studies was 10.9 years (range 5-17.8 years). The mean follow-up specifically in the AM and TT groups were 10.8 years (range, 5.4-17 years) and 11.4 years (range, 6-17.8 years), respectively. A total of 783 (50.6%) patients underwent TT ACLR. Of these patients, 401 (49.3%) developed radiographic PTOA. A total of 763 (49.4%) patients underwent AM ACLR. Of these patients, 324 (mean: 21.8%) went on to develop radiographic PTOA. Meta-analysis demonstrated a significantly greater rate of PTOA following ACLR using a TT technique compared to an AM reconstruction technique overall (49.3% vs.25.4%, p<0.001) and when studies were stratified by 5-10 (53.7% vs. 14.2%, p<0.001) and at greater than 10 year (45.6 % vs. 31.2%, p<0.001) follow-up. Conclusions: Transtibial ACLR is associated with higher overall rates of radiographic PTOA compared to the AM ACLR approach. The rates of radiographic PTOA following ACLR with a TT approach are also significantly higher than using an AM approach when stratified by length of follow-up (5-10 and greater than 10-year follow-up).